Least Risk Bomb Location Explosives Identification, Detection and Mitigation (Global Journal of Management and Business Research, 2021)
This paper investigates the still evolving strategic trajectories and the context adopted for the procedures for inducting a Least Risk Bomb Location (LRBL) that began with discretionary participation by various aircraft manufacturers approximately in the year 1972, where the use of a specific procedure has been designed to decrease the effects of an explosion significantly in the aircraft#x2019;s passenger cabins of large commercial airplanes. Additionally, the International Civil Aviation Organization (ICAO) has provided the information on the location of the LRBL and guidance to various operators (National/International) on the procedures to use when a suspected threat item is found on-board an airplane. The designation of LRBL for aero planes is intended to be used solely for the transport of cargo, where an aero plane must include a designated location where a bomb or other explosive device could be designated to protect integrity of the structure and flight-critical systems from damage in the case of detonation occurs.
Keywords: aviation study; flight-critical structures; bomb; damage on detonation